Analysis of Mutations in Conserved and Susceptible Regions Across the Whole Genome Sequencing Analysis for SARS-CoV-2 in Iraqi Patients - Abed Alhussien, Thaer A.; Fadhil , Hula Y. (Iraqi Journal of Science, 2023)
This study aimed to get a better understanding of molecular epidemiology and genetic variation in the spike glycoprotein as a key viral component involved in viral entrance into host cells and as a potential vaccination target. Three Iraqi SARS-CoV-2 strains were investigated using whole-genome sequencing, with two of them clustering into the 20A (GH) clade, and the remaining strain is clustered in 20E (GV) clade, belonging to the B.1.36.1 and B.1.177.80 lineage, respectively. Whole-genome sequencing of the viral RNA samples revealed nine sporadic nonsynonymous uncommon mutations with frequency ranged from 0.00 to 0.19%. The ORF1ab, ORF1a, ORF3a, S, N, intergenic, ORF7 and ORF8 areas have seen the most changes. Furthermore, in all of our sequences, we discovered a D614G (aspartic acid to glycine) mutation in spike protein that co-occurred with an NSP12 P323L (viral RNA-dependent RNA polymerase) mutation. The findings point to several viral introductions in Iraq and provide new genetic information on SARS-CoV-2 at the worldwide level. Pathogenesis, diagnostics  and vaccine development require information such as SNPs and mutations.